EFFECT OF DIETARY SUPPLEMENTATION OF RUMEN PROTECTED RAPESEED OIL ON MILK OMEGA-3 FATTY ACID PROFILE OF LACTATING CROSSBRED COWS - G. Subrahmanyeswar; S. Senthil Murugan; Sanies Juliet; C. Sudharsan; Biju Chacko (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The effect of rumen protected omega–3 fatty acids prepared from polyunsaturated fatty acids (PUFA) rich rapeseed oil on milk fatty acid profile of lactating crossbred cows have been studied in this experiment. Eighteen lactating crossbred cows were selected and divided randomly into three groups (GI, GII and GIII) with six animals in each group. All the animals in GI were fed with basal diet (concentrates and green roughage ad libitum). In GII and III group cows, rumen protected fatty acids were mixed with basal diet before feeding. The calcium fatty acids of rapeseed oil (CaRSO) and encapsulated rape seed oil were fed to GII and GIII group cows respectively, for 90 days of experimental period. The fatty acid profile of milk, rapeseed oil and bypass fat was analysed by gas chromatography. The supplementation of CaRSO and encapsulated rapeseed oil significantly (P<0.05) increased milk yield compared to control. Better production efficiency (P<0.01) and increased 4 per cent FCM (kg/day) was recorded in encapsulated fatty acid supplemented group compared to CaRSO. The total concentration of omega-3 fatty acids (alpha linoleic acid, eicosapentaenoic acid and docosahexaenoic acid) were detected in milk of treatment group cows compared to control group.